Deflecting a “crisis”: the opioid epidemic in Appalachia as state violence - Pitman, Brian (Contemporary justice review, 2023)
Drug overdoses are the number one preventable death in the United States. In 2022, over 109,000 people died as a result of a drug overdose. The rise in drug overdose deaths has corresponded with the US government’s neoliberal turn, which refuses to intervene in markets, expands the security state, and individualizes social issues. In this paper, we argue that this crisis is the result of state violence. More specifically, the state set the framework for responding to the crisis with the War on Drugs that began in the 1980s. The opioid crisis emerged due to the state deregulating the pharmaceutical industry, leading to the distribution of opioids across the country, but that were disproportionately distributed to the Appalachian region. When the state finally did respond, its response further entrenched criminalization as the state’s approach left a vacuum of people addicted to opioids forced to turn to the illegal heroin and fentanyl drug markets that exacerbated death rates further. Finally, the state continues to largely ignore and demonize harm reduction alternatives in lieu of expanding the prison industrial complex further. This, we argue, is state violence.